Automatic night lamp with morning alarm - Azizan, Anis Syazwani; Mohamad Azhar, Fatin Noorsyafiqah (2016)
The automatic night lamp with morning alarm is actually designed to helps us have a better sleep at night and wake us up in the morning. This device should be able to give a soft glow by the LED at night in order to helps people sleep better and who have problems such as afraid of the dark. While in the morning, the alarm or the buzzer should produce a sound that able to wake them up. The project is aimed to be a useful device that helps people and make their life easier as the device is an automatic one and the people do not have to trouble themselves to set the alarm. They just need to switch on the power supply and the device is ready to function. This project consists of two parts which is software and hardware. The software part is all about the programming written in MPlab software and the circuit construct as in Proteus 7. As for the hardware part, it represents the fabrication of PCB and all the components used.